Sarcoid Nodule or Lung Cancer? A High-Resolution Computed Tomography-Based Retrospective Study of Pulmonary Nodules in Patients with Sarcoidosis - Chiara Catelli; Susanna Guerrini; Miriana D’Alessandro; Paolo Cameli; Antonio Fabiano; Giorgio Torrigiani; Cristiana Bellan; Maria Antonietta Mazzei; Piero Paladini; Luca Luzzi (Diagnostics)
Background: The objective of this retrospective study was to compare the characteristics of sarcoid nodules and neoplastic nodules using high-resolution computed tomography (HRCT) in sarcoidosis patients. Methods: This is a single-center retrospective study. From 2010 to 2023, among 685 patients affected by pulmonary sarcoidosis, 23 patients developed pulmonary nodules of a suspicious malignant nature. The HRCT characteristics of biopsy-proven malignant (Group A) vs. inflammatory (Group B) nodules were analyzed and compared. Results: A significant difference was observed between the groups in terms of age (p = 0.012). With regard to HRCT features, statistical distinctions were observed in the appearance of the nodule, more frequently spiculated in the case of lung cancer (p < 0.01), in the diameter of the nodule (Group A: 23.5 mm; Group B: 12.18 mm, p < 0.02), in the median nodule density (Group A: 60.0 HU, Group B: −126.7 HU, p < 0.01), and in the number of pulmonary nodules, as a single parenchymal nodule was more frequently observed in the neoplastic patient group (p = 0.043). In Group A, the 18-PET-CT demonstrated hilar/mediastinal lymphadenopathy in 100% of cases; histology following surgery did not report any cases of malignant lymph node involvement. Conclusions: An accurate clinical evaluation and HRCT investigation are crucial for diagnosing lung cancer in patients with sarcoidosis in order to determine who requires surgical resection. The spiculated morphology of the nodule, greater size, the number of pulmonary nodules, and density using HRCT appear to correlate with the malignant nature of the lesion.